# tellPearson: the activist 'public education' network. Issue 3 (4th May 2018) - Hogan, Anna
ABSTRACT: This paper investigates the contemporary nature of education activism in the context of the Global Education Industry (GEI). Theorising around contentious politics, the activist teaching profession, and notions of 'connective' action, suggests that educational activists are now using social media to oppose the increasing commercialisation of education. This paper focuses on the '#tellPearson' campaign to explore how Twitter was leveraged as a social space to promote a campaign against the activities of Pearson plc. Analysis of this Twitter network shows how new social structures are being used to frame issues, mobilise resources and promote stakeholder action. While it is difficult to offer definitive conclusions about the success of this campaign, it is possible to reflect on the strategies now being used to hold those in positions of power and influence in the GEI to account.